Exploring the teaching and learning indicators towards education 4.0 in MTUN, Malaysia - Mat Jam, Nor Aishah; Puteh, Saifullizam (2022)
MTUN has been given responsibility for producing skilled TVET workforces in the industrial sectors. Therefore, the education structure in MTUN is gradually making a transition to Education 4.0 to integrate the existing education structure with the discovery of the 4th Industrial Revolution new technologies. The impact of this shift demands changes in the implementation of teaching towards Education 4.0. Teaching towards Education 4.0 is a phenomenon in moving the change of MTUN to a higher level. However, there is an issue of a mismatch of skills between the industry's needs and graduates' quality to face the 4th Industrial Revolution in Malaysia. Therefore, this study explores how to implement Education 4.0 to produce quality and technologically skilled graduates required by the industry. Thus, this study aims to determine the indicators and elements of teaching towards Education 4.0 for Engineering Technology in MTUN. The study involved seven experts in instructional design technology and in Technical Vocational Education and Training (TVET). The interview data collections were analysed using thematic analysis to explain the subject matter of this study. Eight elements were identified to implement teaching towards Education 4.0. These include Industry 4.0 elements, courses design, projects, practical, simulation, educator readiness, up-skilling and re-skilling training, and industrial experience. These elements may be viewed in two mains constructs which are essential to implement in the Engineering Technology programme in MTUN. There are curriculum and educator professional development. Further studies, which take these variables into account will need to be undertaken.